Can the Dustiest Main Sequence Stars Tell Us About the Rocky Planet Formation Process?. Issue Volume 10:Issue S314(2015) (November 2015) - Melis, Carl
Abstract: Main sequence stars hosting extreme quantities of inner planetary system debris are likely experiencing transient dust production events. The nature of these events, if they can be unambiguously attributed to a single process, can potentially inform us on the formation and/or early evolution of rocky Earth-like planets. In this contribution I examine some of the dustiest main sequence stars known and three processes that may be capable of reproducing their observed properties. Through this activity I also make an estimate for the likelihood of an A-type star to have an asteroid belt-like planetesimal population.